Analisis Upaya-upaya Penurunan Berat Badan pada Wanita Usia Produktif di Wilayah Kerja Puskesmas Wawonasa Kecamatan Singkil Manado - Rahamis, Dwi Christiani Audri; Ratag, Gustaaf A.E.; Mayulu, Nelly (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2014)
Obesity is one of the taxing healthy problems, therefore prevention and treatment become priority in health field. Thetreatment intervention is referred to weight decreasing. The most nutrient problem for adult above 18 years old is overweightand obese. Obesity prevalency is dominated by woman as big as 26,9%. At Wawonasa Public Healthy Centre study2013, showed that 41,6% respondents are included in obese nutrient status.The research aims to analyze the weight decreasingeffort for productive women in Wawonasa, Singkil Manado, Public Health Centre. This research uses QualitativeMethod and it is hold in Wawonasa Singkil Manado Public Health Centre on November 2013 up to January 2014. The informantaking uses Purposive Sampling and it is obtained 10 informans who give a deep interview. The data analysis usescontent analysis and triangulation technique (source and method) to make analysis be valid. The productive women inWawonasa Singkil Manado public healthy Centre realize the effect of obesity and do some efforts of weight decreation bydoing exercise or sport, decreasing of food portion and its frequency, consuming diet product, fasting and smoking. However,in doing the efforts, there are some barriers faced, such as: wrong diet program, unable to hold food appetite andthere is no support from husband.Keywords: Obesity, Productive Women, Effort of Weight Decreation